2005
DOI: 10.1111/j.1469-8137.2005.01479.x
|View full text |Cite
|
Sign up to set email alerts
|

Virus infection in remnant native bunchgrasses from invaded California grasslands

Abstract: Summary• This study examined the effects of infection with barley and cereal yellow dwarf viruses (BYDVs) on wild grass species in California, a region in which native perennial bunchgrasses have been largely replaced by exotic annual grasses. We sought to determine whether these widespread viruses compromise the fitness of wild hosts and thus have the potential to influence grassland dynamics. Plant viruses have been long overlooked in ecological studies, and their influence on wild hosts has often been assum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
141
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(153 citation statements)
references
References 66 publications
(80 reference statements)
5
141
3
Order By: Relevance
“…This could act as a biological barrier stopping TSV-parthenium persisting in crownbeard populations and provide parthenium with a biological advantage over crownbeard in locations where they are found together. A similar synergistic plant-virus interaction was also described by Malmstrom et al (2005) who described a plant community shift in favour of virus-tolerant grass species over susceptible native grasses. There may be variation in the reaction of TSV-parthenium isolates infecting crownbeard and testing with further isolates would help to clarify if the effect on crownbeard seed is consistently observed.…”
Section: Discussionmentioning
confidence: 69%
“…This could act as a biological barrier stopping TSV-parthenium persisting in crownbeard populations and provide parthenium with a biological advantage over crownbeard in locations where they are found together. A similar synergistic plant-virus interaction was also described by Malmstrom et al (2005) who described a plant community shift in favour of virus-tolerant grass species over susceptible native grasses. There may be variation in the reaction of TSV-parthenium isolates infecting crownbeard and testing with further isolates would help to clarify if the effect on crownbeard seed is consistently observed.…”
Section: Discussionmentioning
confidence: 69%
“…Even if no general trend arises from results concerning viral mutant genotypes, such studies demonstrate the existence of variation in the relationships between viral accumulation and virulence or symptom severity. Unfortunately, studies that reported the phenotype of natural isolates often measured only virulence (Yahara & Oyama 1993;Lapidot et al 1997;Maskell et al 1999;Funayama-Noguchi 2001;Malmstrom et al 2005Malmstrom et al , 2006 or viral accumulation (Fargette et al 1987;Llamas-Llamas et al 1998;Thurston et al 2001;Untiveros et al 2007;Wintermantel et al 2008) of one viral isolate in one or several host genotypes in different environments. To our knowledge, only a handful of studies have measured both phenotypes concomitantly for several viral natural isolates after individual inoculation of one host genotype.…”
Section: Viral Accumulation Versus Virulencementioning
confidence: 99%
“…Barley and cereal yellow dwarf viruses (hereafter we refer to this complex of phloem-limited luteoviruses as BYDV) are one of the most economically important pathogens in grasses worldwide, causing stunting and yield losses in grain crops such as wheat, barley, and oats (26), and they are among the most prevalent of all viral pathogens (27). In California grasslands, BYDV is a persistently present disease, with occasional epidemic outbreaks (28); it infects a broad range of native and introduced grasses, leading to increased mortality and lower fecundity (29); and its origin is as yet unknown. The pathogen is persistently transmitted by at least nine aphid species in California (30,31).…”
mentioning
confidence: 99%